Cardiovascular Toxicities of Breast Cancer Treatment: Emerging Issues in Cardio-Oncology - Sharad Goyal; Bruce George Haffty (Frontiers Media SA, 2021)
Cancer and cardiovascular disease (CVD) are the two most common causes of mortality and morbidity worldwide. The incidence of both cancer and cardiovascular disease increases with age. With increased life expectancy, the burden of both these diseases will increase substantially in coming years. Patients with CVD share multiple common risk factors and lifestyle behaviors in addition to frequently suffering from multiple comorbid conditions. Tobacco use, hypertension, high cholesterol, diabetes, physical inactivity, and poor nutrition are all established risk factors of heart disease. Patients with diseases such as breast cancer may develop CVD from treatment, such as use of chemotherapy and RT. Effects on the heart are a potentially significant and serious clinical problem in radiation therapy treatment of breast cancer. Over the course of the past 50 years, there have been great advances in the delivery of RT due to the development of new techniques, beam energy, improvement in imaging modalities, and development of image registration strategies. It is hypothesized that cardiac damage from RT is correlated to the dose absorbed by the heart and differs between left- and right-breast radiotherapy. The damage to cardiac micro- and macro-vasculature is the pathophysiological cause of RT-related heart disease. Given the growing clinical relevance of cardio-oncology, this Frontiers in Oncology Research Topic provides a venue for disseminating focused reviews and cutting edge research in this quickly growing field. We encourage submission of original papers and reviews dealing with cardiac toxicity after breast cancer treatment, motion management to reduce cardiac exposure, imaging to evaluate potential cardiac toxicities and primary prevention of cardiac disease in the breast cancer patient.